Optimalisasi Produksi Benih Udang Vanamei (Litopenaeus vannamei) melalui Stimulasi Kualitas Pakan Alami di Kabupaten Tuban - buwono, nanik retno; Musa, Muhammad; Lusiana, Evellin Dewi; Afifah, Kharisma Latifatul; Nikmah, Munauw Weretun; Maulana, Abdullah Radhi (Universitas Muhammadiyah Surakarta, 2025)
This community service program was conducted with the Benur Barokah Group (Tuban Regency), a producer of vannamei shrimp (Litopenaeus vannamei) post larvae at the PL-5 stage. Major constraints included inconsistent natural feed quality, water-quality management based mainly on experience, and limited marketing, leading to low harvest success (≈40% of stocked PL-5) and fluctuating survival rates. The program aimed to improve seed production by mentoring partners on Chlorella sp. microalgae culture as natural feed, training on routine water-quality monitoring, and providing measuring tools (digital thermometer and refractometer), supported by an operational culture module. A website was also developed to broaden marketing reach. Methods included site surveys, socialization and extension sessions, hands-on mentoring, and monitoring and evaluation. Outcomes included improved partner understanding of microalgae culture and key water-quality parameters, availability of monitoring instruments, and the establishment of digital promotional media. Questionnaire-based evaluation indicated highly positive partner responses. Sustainability will be supported by appointing responsible personnel, scheduling routine culture activities and water-quality record keeping, and periodically updating digital marketing content.